Edukasi Personal Hygiene Pada Anak Usia Dini dengan G3CTPS - Ni Wayan Wiwin Asthiningsih; Tri Wijayanti (Jurnal Pesut : Pengabdian untuk Kesejahteraan Umat, 2019)
ABSTRACT Early childhood is a golden age to instill clean and healthy behavioral values (PHBS), so that it has the potential as a change agent to promote PHBS, both in the school environment, family and community. Providing early education about personal hygiene to children, especially how to brush teeth properly can prevent dental caries from rarely brushing teeth. Getting used to washing hands with soap in children can prevent diseases caused by bacteria, such as diarrhea, typhoid, and so on. The purpose of this activity was to improve the health status of pre-school age children through health education about brushing their teeth properly and washing their hands with soap. This activity was carried out in pre-school age children in PAUD Kebun Kita, TK IT Az Zahra, dan PAUD Pelita Bunda, working area of Puskesmas Juanda Samarinda. As a result of this community service activity, all pre-school children was able and enthusiastic in practicing 7 steps of washing hands and how to brush their teeth properly. Pre-school children were also able to answer questions given about the importance of brushing and washing hands. Keywords: education, personal hygiene, G3CTPS